Uwagi dotyczące wykonywania kary pozbawienia wolności w przywięziennych Domach dla Matki i Dziecka - Sitnik, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Problems arising due to adoption of a course of action in respect to convicted women, constitute an important aspect of penitentiary nature. Other issue, which arouses much controversy, concerns the children who live with their mothers in correctional facilities located within premises of prison facilities. Correctional Facilities for Women and their Children have long been recognized in the Polish jurisdiction and despite criticism they had received, the Penal Executive Code still maintains this institution in force. In Poland there are two facilities designed for incarcerated mothers and their children: Correctional Facility no. 1 in Grudziądz, comprising only a delivery-gynecological room as well as a Facility for Small Children, and Correctional Facility in Krzywaniec comprising a Facility for Mothers and their Children. The purpose of this article is to make its readers familiar with chosen problems related to the execution of imprisonment in respect to women who are serving sentences together with their children.
Keywords: kobieta; wykonywanie kary pozbawienia wolności; przywięzienne Domy dla Matki i Dziecka; dziecko w izolatce; żłobki więzienne